Zooborns! When I'm big - Bleiman, Andrew (Beach Lane Books, 2025)
"As the baby ZooBorns animals grow up, their fur changes color, spots and stripes come and go, and horns grow in, but they stay as adorable as ever"-- Provided by publisher.